MODELING OF THE PROCESS OF FORMATION OF INDIVIDUAL MARKETING DEMAND: A COMPARATIVE ANALYSIS AND GENERALIZATION OF THE PRECEDING CORRESPONDING RESULTS - Anatoly V. Korotkov (Статистика и экономика, 2016)
The article focuses on the modeling of series-STI formation of individual market demand. The analysis, and then sum-of three well-known inmarketing models, which exhaust the currentlyknown approaches is revised. The article shows that all three models have a signiﬁ cant difference in the number of stages and terminology. The obtained results are the basis for the developmentof the author’s model of gradual development of demand - «need - desire - requirement -demand» or abbreviated as «model NDRD» and can be considered as a contribution to the methodology of study a demand.